Semipapposides A-M, triterpenoid bidesmosides saponins from the roots of Scabiosa semipapposa. (December 2020) - Bendamene, Samia; Boutaghane, Naima; Bellik, Yuva; Sayagh, Charlotte; Alabdul Magid, Abdulmagid; Harakat, Dominique; Kabouche, Zahia; Voutquenne-Nazabadioko, Laurence
Abstract: Phytochemical investigations of the roots of Scabiosa semipapposa Salzem ex D.C. have led to the isolation of 12 undescribed triterpenoid saponins named semipapposides A-L, one undescribed saponin semipapposide M obtained as an inseparable mixture, together with three known oleanolic acid glycosides. Their structures were elucidated by analysis of 1D and 2D-NMR ( 1 H– 1 H COSY, TOCSY, HSQC-TOCSY, HSQC, ROESY or NOESY, and HMBC) spectroscopic data and mass spectrometry (HR-ESI-MS), and by comparison with those of related metabolites. All saponins possess a partial sequence rhamnopyranosyl-(1 → 2)-xylopyranosyl or rhamnopyranosyl-(1 → 2)-arabinopyranosyl- at C-3 of the aglycon and a gentiobiose unit at C-28. These results represent a contribution to the knowledge of the saponins of Scabiosa species and their chemotaxonomy. Graphical abstract: Image 1 Highlights: Scabiosa semipapposa Salzem ex D.C collected in Algeria was phytochemically investigated. Thirteen previously undescribed triterpene saponins were isolated. Their structures were elucidated by 1D, 2D-NMR and HRESIMS analyses. This is a contribution to the chemotaxonomy of the genus Scabiosa .